Distribution and Occurrence of Amblyomma maculatum sensu lato (Acari: Ixodidae) and Rickettsia parkeri (Rickettsiales: Rickettsiaceae), Arizona and New Mexico, 2017–2019. Issue 6 (10th July 2020) - Hecht, Joy A; Allerdice, Michelle E J; Karpathy, Sandor E; Yaglom, Hayley D; Casal, Mariana; Lash, R Ryan; Delgado-de la Mora, Jesus; Licona-Enriquez, Jesus D; Delgado-de la Mora, David; Groschupf, Kathleen; Mertins, James W; Moors, Amanda; et al.
Abstract: Amblyomma maculatum Koch sensu lato (s.l.) ticks are the vector of Rickettsia parkeri in Arizona, where nine cases of R. parkeri rickettsiosis have been identified since the initial case in 2014. The current study sought to better define the geographic ranges of the vector and pathogen and to assess the potential public health risk posed by R. parkeri in this region of the southwestern United States. A total of 275 A. maculatum s.l. ticks were collected from 34 locations in four counties in Arizona and one county in New Mexico and screened for DNA of Rickettsia species. Rickettsia parkeri was detected in 20.4% of the ticks, including one specimen collected from New Mexico, the first report of R. parkeri in A. maculatum s.l. from this state. This work demonstrates a broader distribution of A. maculatum s.l. ticks and R. parkeri in the southwestern United States than appreciated previously to suggest that R. parkeri rickettsiosis is underrecognized in this region.